Assays of fibrin network properties altered by VKAs in atrial fibrillation – importance of using an appropriate coagulation trigger - Ząbczyk, Michal; Blombäck, Margareta; Majewski, Jacek; Karkowski, Grzegorz; Wallen, Hakan N.; Undas, Anetta; He, Shu (Thrombosis and Haemostasis, 2015)
Atrial fibrillation (AF) is a prothrombotic condition, involving increased thrombin generation and fibrinogen concentrations. Vitamin K antagonists (VKAs) prevent arterial thromboembolism if optimal anticoagulation is achieved by individualised drug doses, assessed by determining the Prothrombin time-related International Normalized Ratio (Pt-INR). There is evidence that formation of tight-laced fibrin networks is pathogenic in prothrombotic diseases. This study was performed among AF patients, to test whether long-term treatment with VKAs affects the structure of fibrin networks, and whether the effect is altered by employing different coagulation triggers: exogenous thrombin (1 IU/ml), 10 pM tissue factor (TF) or a commercial Pt-INR reagent (containing 400-fold more TF). In the thrombin-based method, fibrin network porosity (scanning electron microscopy) and liquid permeability (flow measurements) correlated inversely to fibrinogen concentrations, while positive correlations to the degree of anticoagulation were shown with the Pt-INR reagent. In the method with 10 pM TF, the two above relationships were detected, though the influence of Pt-INR was more profound than that of fibrinogen concentrations. Moreover, greater shortening of clot lysis time (CLT) arose from more permeable clots. As a coagulation trigger, 10 pM TF vs exogenous thrombin or the Pt-INR reagent is more informative in reflecting the in vivo process from thrombin generation to fibrin formation. Since fibrin network permeability rose in parallel to elevations of INR and shortening of CLT in AF patients, antithrombotic effects on prevention of thrombotic complications may be achieved from impairment of thrombin generation, resulting in formation of permeable clots susceptible to fibrinolysis.
Keywords: Atrial fibrillation; vitamin K antagonists; fibrin network permeability; Pt-INR; coagulation trigger